Mountain wave motions determined by the Esrange MST radar - Réchou, Anne; Barabash, V.; Chilson, P.; Kirkwood, S.; Savitskaya, T.; Stebel, K. (HAL CCSD, 1999)
International audience A European campaign of ground-based radar, lidar and optical measurements was carried out during the winter of 1996/1997 (28 December-2 February) to study lee waves in the northern part of Scandinavia. The participants operated ozone lidars, backscatter lidars and MST radars at ALOMAR/Andoya and Esrange/Kiruna, and an ALIS imaging system in Kiruna. The Andoya site was generally windward of the Scandinavian mountains, the Kiruna site on the leeward side. The goal of the experiment was to examine the influence of lee waves on the formation of Polar Stratospheric Clouds (PSCs). This paper studies the radar data from MST-radar ESRAD located at Esrange [68. ° N, 21. ° E], i.e. in the lee of the mountains. We present three cases where strong lee waves were observed: in one case they propagated upwards to the lower stratosphere and in the other two cases they were trapped or absorbed in the troposphere. We examine the local waves and the direction and strength of the local wind using the radar, the synoptic meteorological situation using weather maps (European Meteorological Bulletin) and the synoptic stratospheric temperatures using ECMWF data. We observed that waves propagate up to the stratosphere during frontal passages. When anticyclonic ridges are present, the propagation to the stratosphere is very weak. This is due to trapping of the waves at or below the tropopause. We also show that the radar data alone can be used to characterise the different weather conditions for the three cases studied (through the variation of the height of the tropopause). The synoptic stratospheric temperatures in the three cases were similar, and were above the expected threshold for PSC formation. Lidar and visual observation of PSCs and nacreous clouds, respectively, showed that these were present only in the case when the lee waves propagated up to the lower stratosphere.